Black TiO2 nanotubes: Efficient electrodes for triggering electric field-induced stimulation of stem cell growth - Mazare, Anca Valentina; Park, Jung Hyun; Simons, Sebastian; Mohajernia, Shiva; Hwang, Imgon; Yoo, Jeong Eun; Schneider, Christopher; Fischer, M. J.; Schmuki, Patrik (Acta Biomaterialia, 2019)
TiO2 nanostructures represent a key platform for biomedical applications, due to the combination of biocompatibility and high surface area. Especially TiO2 nanotube layers have been widely investigated due to controllable nanotopographic effects as well as for electrodes in electrostimulation experiments. In the present work we produce Ar/H2-reduced ‘black’ TiO2 nanotube arrays with a strongly enhanced electrical conductivity and explore their interaction with mesenchymal stem cells when used as electrodes to apply electric fields (EF) across the cells. While we observe no significant change in cell adhesion and their focal contact formation on these high conductivity nanotubes, we do observe a rapid stem cell response when EF is engaged using the ‘black’ TiO2 nanotube arrays as electrodes. Compared to as-formed nanotube arrays, a faster stem cell growth was observed and a lower EF intensity caused an intracellular calcium level elevation. Our results indicate that the increased conductivity in TiO2 nanotubes significantly enhances the early stem cell response to minimal electric field stimuli. Statement of Significance: The use of TiO2 nanostructures in biomedical applications is widely investigated, especially considering the nanostructured surface influence on the biomaterial-cell interactions. We have previously shown that an applied electric field (EF) on stem cells grown on TiO2 nanotubes leads to synergistic osteogenic stimulation in the absence of biochemical bone-inducing supplements. Here we report that black (i.e. highly conductive nanotubes obtained by reduction treatments) TiO2 nanotubes enable short-time EF effects on stem cells: we observe a faster stem cell growth and a significantly enhanced early stem cell response to minimal EF stimuli. The application of such nanostructures under electric field is promising for therapeutic interventions for bone regeneration and tissue engineering approaches.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Electric field; Reducing treatment; Stem cells; TiO